KOMPETENSI, KOMPENSASI, KOMITMEN ORGANISASI DAN KINERJA PERANGKAT DESA DI KECAMATAN KERUAK LOMBOK TIMUR - Luksanti, Nirmala Rahayu; Hadiyati, Ernani; Muawanah, Umi (Universitas Hamzanwadi, 2023)
The aim of this research is to examine and analyze the influence of competence, compensation and organizational commitment on the performance of village officials in Keruak District, East Lombok Regency. The data analysis technique uses multiple linear regression. The results of the analysis show that simultaneously it has a significant influence on the performance of village officials. Partially, the variables of competence and organizational commitment each have a significant positive influence on the performance of village officials. Meanwhile, the compensation variable has no influence on the performance of village officials in Keruak District, East Lombok Regency. The coefficient of determination value on the adjusted R square was obtained at 30.1%. This means that 30.1% of the performance of village officials in Keruak District, East Lombok Regency is influenced by the variables of competency, compensation and organizational commitment.